Is exercise good for high blood pressure?. Issue 6344 (18th September 1982) - Wilcox, R G; Bennett, T; Brown, A M; Macdonald, I A
Abstract : Ten men with uncomplicated essential hypertension (mean standing blood pressure 165/109 mm Hg) and 10 normal controls matched for age and weight were studied for the hypotensive potential of moderate exercise. Tests were conducted on a treadmill set to induce a steady heart rate of 120 beats/min and performed over five 10-minute periods separated by three minutes' rest and finishing with 30 minutes' sitting quietly in a chair. During exercise the mean systolic pressures were identical in the hypertensive patients and controls (175±SEM 5 mm Hg), the controls therefore sustaining an appreciably greater increase in pressure. During the 30-minute rest period after the tests both the control and hypertensive groups showed a significant and sustained fall in absolute systolic pressures as compared with pre-exercise values (p <0·001), the mean percentage reductions being 22% and 25% respectively. If a fall in blood pressure after exercise is maintained for four to 10 hours, then a "good walk" twice a day might be reasonable treatment for mild hypertension. Studies are continuing to determine the amount of exercise needed and the duration for which the reduction in blood pressure is maintained.